URGENSI INVESTASI: EDUKASI LITERASI KEUANGAN BAGI IBU RUMAH TANGGA - Rina Susanti; D Ririn Indriastuti; Rina Wulandari (Komunitas Dosen Indonesia, 2025)
Housewives has an important role in managing household management in order to achieve family happiness and prosperity. One of the important roles of a housewife is managing family finances. This is based on the fact that it is the housewife who often plays the role of managing the income received by the family which is then managed to meet the family's needs. Considering the important role of housewives in managing family finances, financial literacy is very important for housewives themselves. The financial literacy education carried out includes socialization and assistance to housewives in managing household finances. The socialization material includes the distribution of income for consumption needs, emergency fund savings, and investment for future financial planning, as well as social needs such as zakat and mandatory contributions. Next, assistance is provided for housewives who are willing and still have problems in managing their finances and therefore require further consultation and guidance. By carrying out this activity, it is hoped that the financial literacy of housewives, especially in Joglo sub-district, can increase. This can then be followed by increasing family welfare through better financial management